Diagnosis, treatment planning, and full-mouth rehabilitation in a case of amelogenesis imperfecta - Mayuri Naik; Siddharth Bansal (Wolters Kluwer Medknow Publications, 2018)
Amelogenesis imperfecta is a genetic condition affecting the teeth resulting in aberrations of the structure and clinical appearance of enamel. The treatment of amelogenesis imperfecta involves a multidisciplinary treatment approach requiring a comprehensive examination, diagnosis, and effective treatment planning strategy along with satisfaction of patient-related factors. The clinical case described here involves judicious involvement of different disciplines to formulate a treatment plan best suitable to confirm with the patient's needs and expectations, at the same time maintaining the integrity and harmony of associated hard and soft tissues.